2019
DOI: 10.1007/s00125-019-4950-x
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression and release of exosomal miRNAs by human islets under inflammatory and hypoxic stress

Abstract: Aims/hypothesis Pancreatic islets produce non-coding microRNAs (miRNAs) that regulate islet cell function and survival. Our earlier investigations revealed that human islets undergo significant damage due to various types of stresses following transplantation and release miRNAs. Here, we sought to identify and validate exosomal miRNAs (exo-miRNAs) produced by human islets under conditions of cellular stress, preceding loss of cell function and death. We also aimed to identify islet stress signalling pathways t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 60 publications
2
40
0
Order By: Relevance
“…These conflicting observations are not surprising for at least three reasons: (1) the bulk of beta-cell death in T1D precedes clinical diagnosis, and hence any increase in circulating miR-375 is possibly missed at the time of sampling; (2) the degree, extent, and dynamics of beta-cell death differ between individuals; and (3) islet compensatory mechanisms and ongoing autoimmunity may influence circulating levels even after disease diagnosis. For instance, our observations in mice suggest that miR-375 levels are significantly elevated in circulation immediately (3-6 h) after streptozotocin administration, subsiding to undetectable levels within 24 h. In the context of islet transplantation, we observed that miR-375 levels increase markedly during islet autotransplantation in patients receiving total pancreatectomy with islet auto transplantation, but normalized to baseline levels 7 days after transplantation [35]. In mice, we also observed elevated miR-375 levels 24 h after human islet transplantation, indicating islet inflammation and damage in the peritransplant period [35].…”
Section: Mirnas As Biomarkers In Type 1 Diabetes (T1d)mentioning
confidence: 66%
See 1 more Smart Citation
“…These conflicting observations are not surprising for at least three reasons: (1) the bulk of beta-cell death in T1D precedes clinical diagnosis, and hence any increase in circulating miR-375 is possibly missed at the time of sampling; (2) the degree, extent, and dynamics of beta-cell death differ between individuals; and (3) islet compensatory mechanisms and ongoing autoimmunity may influence circulating levels even after disease diagnosis. For instance, our observations in mice suggest that miR-375 levels are significantly elevated in circulation immediately (3-6 h) after streptozotocin administration, subsiding to undetectable levels within 24 h. In the context of islet transplantation, we observed that miR-375 levels increase markedly during islet autotransplantation in patients receiving total pancreatectomy with islet auto transplantation, but normalized to baseline levels 7 days after transplantation [35]. In mice, we also observed elevated miR-375 levels 24 h after human islet transplantation, indicating islet inflammation and damage in the peritransplant period [35].…”
Section: Mirnas As Biomarkers In Type 1 Diabetes (T1d)mentioning
confidence: 66%
“…For instance, our observations in mice suggest that miR-375 levels are significantly elevated in circulation immediately (3-6 h) after streptozotocin administration, subsiding to undetectable levels within 24 h. In the context of islet transplantation, we observed that miR-375 levels increase markedly during islet autotransplantation in patients receiving total pancreatectomy with islet auto transplantation, but normalized to baseline levels 7 days after transplantation [35]. In mice, we also observed elevated miR-375 levels 24 h after human islet transplantation, indicating islet inflammation and damage in the peritransplant period [35]. Thus, miR-375 is a useful marker for islet cell damage during transplantation.…”
Section: Mirnas As Biomarkers In Type 1 Diabetes (T1d)mentioning
confidence: 66%
“…Overexpression of miR-29b increased the expression of cleaved caspase-3, which is a typical apoptotic factor (Yuan et al, 2018). Saravanan et al (2019) reported that miR-29b-3p was selectively released in exosomes from inflammation and hypoxia induced islets before apoptosis and cell death, which coincided with activation of endoplasmic reticulum (ER) stress response markers IRE-1α, XBP1, HIF-1α, and CHOP. They also detected the selective release of miR-29b-3p in plasma exosomes after these cells were transplanted into streptozotocin (STZ) diabetic nude mice.…”
Section: Discussionmentioning
confidence: 99%
“…They also detected the selective release of miR-29b-3p in plasma exosomes after these cells were transplanted into streptozotocin (STZ) diabetic nude mice. Therefore, miR-29b-3p might be an early indicator of human islet cell apoptosis during prediabetic conditions (Saravanan et al, 2019). MiR-29b-3p was obviously upregulated in high glucose-induced endothelial cells (Silambarasan et al, 2016), and overexpression of miR-29b-3p could cause insulin resistance in mice (Su et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The increased secretion of extracellular vesicles of trophoblastic origin containing miRNAs into the maternal blood flow due to placental dysfunction in PE can contribute to systemic biological changes. Among the miRNAs circulating in blood plasma, we identified (let-7g-5p, miR-26a-5p, miR-28 (-28-3p, -151a-3p), -30a-5p, -148a-3p, -181 (-181a-5p), -183-5p, -186-5p, -188 (-532-5p), -192-5p, and -320 (-320a), which change their expression in response to oxygen deprivation [18][19][20], oxidative stress (miR-140-3p, -143-3p, -378a-3p) [46], and are associated with immune and inflammatory responses (miR-375) [47], as well as ischemia/reperfusion (miR-423-3p) [48]. In general, our results are consistent with the data of other authors.…”
Section: Discussionmentioning
confidence: 99%